The Role of Transformational Leadership in Management Accountants and the Effects of Managerial Dysfunctional Behavior - Agustina, Lidya; Suharman, Harry; Sumantri, Roebiandini; Agoes, Sukrisno (International Economic Conference of Business and Accounting, 2024)
The phenomenon of budgetary slack behaviour is closely related to the inherent nature of humans as "homo economicus," which refers to the idea that humans act rationally with the primary goal of maximizing their utility or personal gain. Budgetary slack is considered a dysfunctional behaviour that is unethical as it contradicts the norms and ethical codes of accountants. Management accountants, seen as "powerful controllers," play a crucial role in reducing this dysfunctional behaviour of budget slack. This research aims to examine the influence of transformational leadership style on management accountants concerning manager’s budget slack behaviour. The study was conducted using a survey method involving managers from various large public-listed companies in Indonesia. A total of 47 questionnaires were collected and analyzed. The data were analyzed using Partial Least Square. The research findings demonstrate that the transformational leadership style of management accountants influences the manager’s dysfunctional budget slack behaviour. This indicates that the transformational leadership style of management accountants can motivate and direct managers to behave more ethically. The results contribute to the management accounting literature, particularly in investigating the role of management accountants within organizations. Furthermore, this study reveals a relationship between the transformational leadership style of management accountants and employee behavioral changes (reducing unethical dysfunctional behaviour). Therefore, the research suggests that organizations emphasize the practice of transformational leadership style among management accountants in their organizational settings to maintain trustworthy relationships with their followers and ultimately foster an organizational culture.